2020
DOI: 10.1021/acs.est.9b06333
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Melt Inputs of Organophosphate Ester Flame Retardants to the Largest High Arctic Lake

Abstract: Organophosphate esters (OPEs) have been detected in the Arctic environment, but the influence of glacial melt on the environmental behavior of OPEs in recipient Arctic aquatic ecosystems is still unknown. In this study, water samples were collected from Lake Hazen (LH) and its tributaries to investigate the distribution of 14 OPEs in LH and to explore the input of OPEs from glacial rivers to LH and the output of OPEs from LH in 2015 and 2018. Σ14OPE concentrations in water of LH were lower than glacial rivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
(118 reference statements)
0
36
0
Order By: Relevance
“…The PFAS extraction was based on a solid-phase extraction (SPE) procedure using Oasis WAX cartridges (6 cm 3 , 150 mg; Waters) . On the other hand, OPEs and PAHs were extracted using an SPE procedure with Oasis hydrophilic–lipophilic balance cartridges (6 cm 3 , 200 mg; Waters) by following an established methodology , with some modifications. Samples were spiked with recovery standards before the SPE (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The PFAS extraction was based on a solid-phase extraction (SPE) procedure using Oasis WAX cartridges (6 cm 3 , 150 mg; Waters) . On the other hand, OPEs and PAHs were extracted using an SPE procedure with Oasis hydrophilic–lipophilic balance cartridges (6 cm 3 , 200 mg; Waters) by following an established methodology , with some modifications. Samples were spiked with recovery standards before the SPE (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The mean ∑OPEs in surface water from the North Atlantic and the Arctic were 2935 pg/L, 35 comparable to the mean ∑OPEs detected in the surface waters of Canadian Arctic lakes and coastal sites (1714−6435 pg/L) 37 but lower than those detected in surface water from the Arctic Ocean (10,670 pg/ L), 67 Canadian Arctic Ocean (11,000 pg/L), 39 Antarctic Peninsula (11,425−19,392 pg/L), 60 Northwestern Pacific to the Arctic (24,101 pg/L), 46 and Canadian Arctic Lake Hazen and its tributaries (15,509−25,096 pg/L). 40 A relatively higher level of ∑OPEs was reported in Ny-Ålesund (Svalbard, the Arctic), where its ∑OPEs ranged from 8700 to 358,000 pg/L, with a mean of 89,018 pg/L. 33 As one of the northernmost permanent human settlements in the world, the town of Ny-Ålesund is located on the shore of the bay of Kongsfjorden with relatively comprehensive living and supporting facilities, airports, harbors, and 18 permanent scientific research stations organized and built by 11 nations.…”
Section: Occurrence and Environmental Behavior Of Opesmentioning
confidence: 99%
“…In 2015, the annual global consumption volume of OPEs was reported to be 680 000 metric tons, and this number was predicted to keep increasing in the forthcoming years . Given that most OPEs are routinely added rather than chemically bonded to the products, they can be easily released into the environment through volatilization, abrasion, or leaching. ,, A large quantity of OPEs, especially some chlorinated OPEs, are relatively persistent in the environment and difficult to completely degrade. Thus, there have been a growing number of reports on the occurrence of OPEs over the past decades, covering numerous OPEs detected in different environmental matrices or organisms. More importantly, toxicological and epidemiological studies have shown that exposure to some OPEs causes various adverse health effects, such as lipidome homeostasis disorders, endocrine disruption, serum hypertriglyceridemia, and reproductive failure. Considering the toxicity and widespread exposure of OPEs, there is an urgent need to comprehensively identify OPEs in various environmental matrices.…”
Section: Introductionmentioning
confidence: 99%